2019
DOI: 10.3389/fimmu.2019.02307
|View full text |Cite
|
Sign up to set email alerts
|

Bacille Calmette-Guérin Vaccine Strain Modulates the Ontogeny of Both Mycobacterial-Specific and Heterologous T Cell Immunity to Vaccination in Infants

Abstract: Differences in Bacille Calmette-Guérin (BCG) immunogenicity and efficacy have been reported, but various strains of BCG are administered worldwide. Since BCG immunization may also provide protection against off-target antigens, we sought to identify the impact of different BCG strains on the ontogeny of vaccine-specific and heterologous vaccine immunogenicity in the first 9 months of life, utilizing two African birth cohorts. A total of 270 infants were studied: 84 from Jos, Nigeria (vaccinated with BCG-Bulgar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…A randomized controlled trial in Australia showed that BCG Denmark and BCG Japan given at birth induced higher proportions of mycobacterialspecific polyfunctional [IFNγ(+)TNF(+)IL-2(+)] CD4 T cells than BCG Russia (Ritz et al, 2012). The impact of different BCG strains on the ontogeny of vaccine-specific and heterologous vaccine immunogenicity in the first 9 months of life was also examined in two African birth cohorts (Kiravu et al, 2019), where BCG Denmark vaccinated infants mounted significantly higher frequencies of polyfunctional CD4+ T cells, compared with infants vaccinated with BCG Bulgaria and BCG Russia. BCG-naïve adult volunteers immunized with BCG Denmark showed divergent whole blood pro-inflammatory and regulatory T cell responses, with significant induction of polyfunctional [IFNγ(+)TNF(+)IL-2(+)] CD4 T cells and IFNγ production confined to individuals with strong local skin inflammation, compared to regulatory-like CD8 T cell induction in individuals with mild skin inflammation (Boer et al, 2015).…”
Section: Different Bcg Formulations Can Induce Distinct But Broad Ranmentioning
confidence: 99%
“…A randomized controlled trial in Australia showed that BCG Denmark and BCG Japan given at birth induced higher proportions of mycobacterialspecific polyfunctional [IFNγ(+)TNF(+)IL-2(+)] CD4 T cells than BCG Russia (Ritz et al, 2012). The impact of different BCG strains on the ontogeny of vaccine-specific and heterologous vaccine immunogenicity in the first 9 months of life was also examined in two African birth cohorts (Kiravu et al, 2019), where BCG Denmark vaccinated infants mounted significantly higher frequencies of polyfunctional CD4+ T cells, compared with infants vaccinated with BCG Bulgaria and BCG Russia. BCG-naïve adult volunteers immunized with BCG Denmark showed divergent whole blood pro-inflammatory and regulatory T cell responses, with significant induction of polyfunctional [IFNγ(+)TNF(+)IL-2(+)] CD4 T cells and IFNγ production confined to individuals with strong local skin inflammation, compared to regulatory-like CD8 T cell induction in individuals with mild skin inflammation (Boer et al, 2015).…”
Section: Different Bcg Formulations Can Induce Distinct But Broad Ranmentioning
confidence: 99%
“…12 Similar results were reported in another clinical trial which compared BCG-Russia and Denmark. 13 Here too, BCG-Denmark induced a greater magnitude of mycobacteria-specific CD4 + T cell responses and polyfunctionality compared to BCG-Russia. 13 Finally, a very large clinical trial in infants in Guinea-Bissau that compared BCG-Denmark, Russia, and Japan found that BCG-Denmark and Japan were more immunogenic than BCG-Russia.…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 94%
“…Apart from the absence of RD-1, propagation 10,11 There is evidence to suggest that anti-TB protection might vary with the strain of BCG used for vaccination (Table 1). [12][13][14] In Uganda, mycobacterial immune responses between infants vaccinated with BCG-Russia, Bulgaria, and Denmark were compared and it was found that vaccination with BCG-Denmark induced a higher percentage of scarring and anti-mycobacterial immune responses. 12 Similar results were reported in another clinical trial which compared BCG-Russia and Denmark.…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 99%
“…The effect of MMc on the polyfunctionality of BCG vaccine responses (PFS) were assessed using GEE models clustered by individual, a gaussian outcome structure, and an exchangeable correlation matrix. We have previously shown that iHEU infants have altered T cell functionality to BCG (24) and that the type of BCG strain used for vaccination contributes strongly to the magnitude and polyfunctionality of vaccine response elicited in infants (29). We therefore adjusted for BCG strain, HIV exposure, and infant age in our analyses.…”
Section: Statisticsmentioning
confidence: 99%